Tofu Dregs Crackers, Innovation of Industrial Solid Waste Utilization Know Ampeldento Village, Malang Regency - Trisna Martha Nur Susila Kusuma Candra; Rifki Muhamad Azam; Intan Isnaeni; Nurul Maulida Ulviah; Syaidatul Fiza Ma'arif; Nur Fitriyah Ayu Tunjung Sari (Pusat Pengabdian Kepada Masyarakat Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
The tofu industry located in Ampeldento Village, Malang Regency is one of the scale industries MSMEs in the surrounding environment which were founded in 2017. Every day, this industry is able to produce 100 kg tofu with 25 kg of solid waste which is often called tofu dregs. Currently solid waste generated from Tofu production process has been used as a mixture of animal feed. Utilization of solid waste that has not been optimal results in a large volume of tofu solid waste that is wasted. Where does it arise problems in the surrounding environment, namely the emergence of unpleasant odors around the waste disposal site. Based on these conditions required new innovations in the utilization of tofu solid waste. Through the dedication program university community, an innovation is made to utilize tofu solid waste into processed crackers. which method applied to the implementation of service is a society participant. The formulated innovation is expected to be able be a solution to existing conditions. In addition, tofu dregs crackers are expected to become a new commodity to add value to the tofu industry in Ampeldento Village.